Peran Pengasuhan Keluarga Broken Home Terhadap Prestasi Belajar Siswa - Denis Agnestu; Khoirotun Ni'mah; Retno Nuzilatus Shoimah (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2026)
The family is the first and primary educational environment for children and plays a strategic role in shaping personality, attitudes, and learning achievement. However, not all children grow up in harmonious family environments. Broken home family conditions often have an impact on students’ psychological development and learning achievement. This study aims to describe the conditions of broken home families, students’ learning achievement, and the role of family parenting in supporting students’ learning achievement at MI Islamiyah Sunan Giri Lamongan. This research employed a qualitative approach using a case study method. Data collection techniques included interviews, observations, and documentation. The results show that although students come from broken home families, supportive parenting, emotional attention, and learning motivation provided by parents or guardians are still able to encourage improvements in students’ learning achievement. These findings emphasize that the quality of parenting has a greater influence than the integrity of family structure.